An investigation of vibrational analysis, thermodynamics properties and electronic properties of Formaldehyde and its stretch by substituent acetone, acetyl chloride and methyl acetate using first principles analysis - Limbu, Susmita; Ojha, Tulsi; Ghimire, Rishi Ram; Rai, Krishna Bahadur (BIBECHANA, 2024)
This study finds the equilibrium configuration, vibrational analysis, thermodynamic properties, and electronic properties of formaldehyde and its derivatives, namely acetone, acetyl chloride, and methyl acetate, using First Principles Analysis. It emphasizes the impact of substituents on the carbonyl group and the need for this comprehensive analysis. The computational methods employed in this work are Gaussian DFT), GaussSum and Moltran calculations. For formaldehyde, the optimization step starts from the energy of -114.51282 Hartree and gets optimized in the energy -114.5129634 Hartree. Similarly for Acetone, Acetyl chloride and Methyl acetate, optimization step start from -193.74375 Hartree, -613.26 Hartree, -266.805 Hartree and gets optimized in the energy -193.1744033 Hartree, -613.2941798 Hartree, -266.8358066 Hartree. Infrared (IR) spectroscopy is used to analyze vibrational frequencies. The C-H and C=O vibrations are highlighted, showing characteristic peaks for each compound. Heat capacity at constant volume (Cv), heat capacity at constant pressure (Cp), internal energy (U), enthalpy (H), entropy (S) and Gibb’s free energy (G) with change in temperature sharply increase from 10 K to 50 K and decreases the increase in rate from 50 K to 500 K. In the derivative of Formaldehyde, Methyl Acetate has the highest energy gap (i.e. -7.4222 eV) and Acetyl Chloride has the small energy gap (i.e. 5.6137 eV). The Chemical parameters like ionization potential, electron affinity, chemical hardness, chemical potential, electronegativity, electrophilicity index, and chemical softness have been also calculated. Electrostatic Potential (ESP) Surfaces, Molecular Electrostatic Potential (MEP), and Electron Density (ED) are visualized to understand charge distribution and reactivity regions. DOS spectra illustrate the density of electron states per unit energy.